Numerical Analysis / Fourth Edition - Burden Richard L; Faires J. Douglas (Pws-Kent Publishing Company, 1989)
Introduction, Mathematical Preliminaries, Solutions of Equations in One Variable, Interpolation and Polynomial Approximation, Numerical Differentiation and Integration, Initial Value Problems for Ordinary Differential Equations, Direct Methods for Solving Linear Systems, Iterative Techniques in Matrix Algebra, Approximation Theory, Approximating Eigenvalues, Numerical Solutions of Nonlinear Systems of Equations, Boundary Value Problems for Ordinary Differential Equations, Numerical Solutions to Partial Differential Equations, Bibliography, Answers to Selected Exercises, Index.